Preliminary assessment of microplastic pollution in surface waters of the Santos Basin: abundance and diversity in the most important oil and gas exploration hub in Brazil - Hudson Carvalho Ferreira; Gisele Lôbo-Hajdu (Ocean and Coastal Research)
Microplastics (Mps) are pervasive in the surface waters of the Santos Basin, a critical maritime zone along the Southeast coast of Brazil, vital to both fishing and oil production. This study sought to assess potential disparities in the abundance, types, colors, and sizes of microplastics in various locations and seasons near oil and gas exploration areas. Seven stations were sampled using Van Dorn-type bottles during two campaigns, in June 2020 and January 2021, encompassing winter and summer seasons. Concurrently, wind, current, and wave data were recorded to investigate their impact on microplastic distribution. Microparticles were meticulously assessed by counting, classifying, measuring, and photographing using an optical microscope. The results unveiled a considerable concentration of putative microplastics in the Santos Basin surface waters, identifying and collecting a total of 1,006 particles. All sampled stations exhibited some degree of microparticles contamination, with counts ranging from 67 to 272 particles per station. The average particulate concentration stood at 159.7 microparticles per liter (Mp/L). While concentrations varied across sampling points, statistical analysis indicated no significant differences (p = 0.5062 – ANOVA test p < 0.05). Fragmented pieces constituted most (51.8%) of putative microplastics, followed by films (24%) and fibers (16.4%), displaying diverse colors, with blue (31.11%) and transparent (27.63%) being the most prevalent. Particles measuring 50 μm or less comprised over 30%, while those smaller than 400 µm constituted about 90% of the total sampled microparticles. The microparticle concentration for the Santos Basin, 10.6 – 43.17 Mp/L, was surprisingly similar to other regions without oil and gas exploration. This study underscores the high prevalence of microparticles in the Santos Basin and highlights the role of oceanographic factors, including wind, waves, and currents, in shaping the dynamics of microplastic contamination in this economically and ecologically significant region.